Formation of a Novel C11-Acetone Adduct of a Pyrrolobenzodiazepine (PBD) with Loss of Cytotoxicity - Corcoran, David B.; Picconi, Pietro; Chui, Connie K.; Procopiou, George; Pysz, Ilona; Rahman, Khondaker Miraz; Thurston, David E. (Synlett, 2018)
The pyrrolidine-catalysed formation of novel diastereomeric C11-acetone adducts was observed during the chromatographic purification of pyrrolobenzodiazepine (PBD) compounds in the presence of acetone. The mechanism of this reaction was explored and the adducts obtained fully characterised. Talirine, the cytotoxic payload element of the antibody-drug conjugate (ADC) vadastuximab talirine, was also found to form a bis-adduct under similar conditions. A cellular cytotoxicity evaluation of the modified PBD compounds confirmed their lack of cytotoxicity, consistent with loss of the DNA-interactive N10–C11 imine functionality. As well as the new chemistry reported here, given the number of PBD-based ADCs presently in the clinic, this observation may be important for the larger-scale manufacture of PBD-based products.
Keywords: pyrrolobenzodiazepines; PBDs; Stork enamine; DNA-binding, Talirine, ADC.